Analysis of Data and Format for OTDR Integrated in Optical Module - Yuehua Ou; Yan Ren (Dianxin kexue)
In order to satisfy the increasing optical testing requirements in PON，OTDR integrated in optical module is constantly developing.For the PON architecture based on OTDR integrated in optical module，the data transmission function and data analysis function of its OTDR relative interfaces were proposed，the OTDR data file structure and the OTDR data content were analyzed，and the data format of OTDR was defined.Therefore，the universal integrated OTDR data format can be realized.